Hubungan Antara Pola Komunikasi Guru-Siswa Dengan Motivasi Belajar Dalam Pembelajaran Fisika di SMAN 1 Sinunukan Kelas XI - irawan, candra; eni sumanti nasution; Sri Utami Kholilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to analyze the relationship between teacher-student communication patterns and students' learning motivation in physics learning among 11th-grade students at SMAN 1 Sinunukan. The research is based on the importance of effective communication in creating a conducive learning environment, especially in physics, a subject often perceived as difficult by students. This study employed a quantitative method with a correlational approach. Data were collected through questionnaires distributed to 31 selected 11th-grade students. The results of the data analysis show a significant and positive relationship between teacher-student communication patterns and students' learning motivation, with a correlation coefficient (r) of 0.870 and a significance value (p) of 0.000. Furthermore, teacher-student communication patterns account for 75.6% of the variance in students' learning motivation. These findings highlight that open, empathetic, and two-way communication between teachers and students greatly contributes to enhancing students’ enthusiasm and interest in learning, particularly in challenging subjects like physics. This study is expected to offer practical insights for teachers in developing more interactive and effective communication strategies to improve student learning outcomes.